Temporal and spatial transferability in telemetry-based dynamic species distribution models: The effects of algorithms and pseudo-absence techniques - Joshua C Wilson; Philip N Trathan; Hugh J Venables; Horst Bornemann; Rochelle Constantine; Daniel P Costa; Luciano Dalla Rosa; Louise Emmerson; Ari S Friedlaender; Michael E Goebel; Simon Goldsworthy; Mark A Hindell; et al. (Ecological Modelling, 2026)

Dam-induced disruption of hydrochory and macrophyte recovery in the Brisbane River post-flood - Colin L. Burke; Luke Carpenter-Bundhoo; David T. Roberts; Hannah M. Franklin; Mark J. Kennard (Aquatic Botany, 2026)

Multigenerational exposure to per- and polyfluoroalkyl substances (PFAS) negatively impacts the reproductive health of male mice - Leah Gillespie; Jacinta H. Martin; Amanda L. Anderson; Natalie A. Trigg; John E. Schjenken; Shannon P. Smyth; Ilana R. Bernstein; Simone J. Stanger; Logan McElhone; Colin C. Conine; Fay Waldrip; Erin J. Campbell; et al. (Environmental Research, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Unprecedented Burning in Tropical Peatlands During the 20th Century Compared to the Previous Two Millennia - Yuwan Wang; Ted R. Feldpausch; Graeme T. Swindles; Patrick Moss; Hamish A. McGowan; Thomas G. Sim; Paul J. Morris; Adam Benfield; Colin Courtney‐Mustaphi; David Wahl; Encarni Montoya; Esther Githumbi; et al. (Global Change Biology, 2026)
Tropical peatland wildfire incidence has risen in recent decades, driven by drainage for land use and intensified by severe droughts with global climate change. These disturbances have altered vegetation structure, disrupted ecosystem functioning, and increased carbon emissions, particularly in Southeast Asia. However, the long‐term history and characteristics of wildfires in tropical peatlands remain largely unknown. Here, we compiled fifty‐eight macro‐charcoal records from peatlands across the tropics, ranging from lowland forested to montane peatlands, to assess millennia‐scale changes and controlling factors of tropical peatland burning. We divided the datasets into four main sub‐regions: Neotropical, Afrotropical, Indomalayan and Australasian ecoregions to explore regional variability. Tropical peatlands had high burning levels between 0 and 850 ce , followed by a relatively low and stable period until a marked increase during the 20th century. The general trend in tropical peatland burning follows changes in global temperature, and climate variables that control the length and severity of drought events have a notable influence on peat burning before 1900 ce . During the 20th century, regional differences were observed, with declining fire trends in the Neotropical and Afrotropical regions and increasing fire trends in the Indomalayan and Australasian regions. This difference is likely attributable to human activities, and such intervention is also evident in palm swamps and hardwood swamps under similar wet, weakly seasonal climates. With the increase in anthropogenic pressures on peatlands and greater climate variability, future wildfires in peatlands are likely to become more frequent and widespread across all tropical ecoregions. Conservation and sustainable land‐use practices could be used to mitigate and control peatland burning and protect these carbon‐rich sinks.

Simulation of polycyclic aromatic compounds in the Athabasca River Basin: integrated models and insights - Qianyang Wang; Maricor J. Arlos; Jinqiang Wang; Mark McMaster; Erin Ussery; Colin A. Cooke; Brandon R. Hill; Nancy Glozier; Keegan A. Hicks (Water Research, 2026)

Basaltic island evolution close to the limits of reef growth: Norfolk Island, Southwest Pacific - Alysha M. Johnson; Mark E. Dickson; Sarah M. Hamylton; Elizabeth Johnstone; Rafael C. Carvalho; Colin D. Woodroffe (Geomorphology, 2026)

FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

Arsenic speciation and mobility in gold mining-impacted riverine sediments from the Loddon River catchment in Victoria, Australia - Francesco Colombi; Ewen Silvester; Aleicia Holland; Darren Baldwin; Colin MacRae; Nick Wilson; Ian Rutherfurd; James Grove; Jodi Turnbull; Mark Macklin; Peter Davies; Susan Lawrence (Applied Geochemistry, 2025)

Wave impacts on vertical cliffs: Insights from laboratory experiments and field observations - Yaxiong Shen; Colin N. Whittaker; Catriona F. Thompson; Alison C. Raby; Adam P. Young; Mark E. Dickson (Coastal Engineering, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Chromophoric dissolved organic matter in the Athabasca Oil Sands Region, Canada, and its association to lake acid sensitivity - Dane Blanchard; Mark Gordon; Huy Dang; Paul A. Makar; Colin Cooke; Yi Yi; Kern Lee; Julian Aherne (Science of The Total Environment, 2025)

The geomorphic evolution of the Tasmantid Seamount Chain - Alysha M. Johnson; Mark E. Dickson; Sarah Hamylton; Colin D. Woodroffe (Marine Geology, 2025)

Salt marsh grass for reducing overtopped flow momentum: Experimental results and XBeach calibration - Joshua Bagg; Mark Battley; Colin Whittaker; Tom Allen; Tom Shand (Coastal Engineering, 2025)

Application of laboratory dam break experiments to non-impulsive wave overtopping - Joshua Bagg; Mark Battley; Colin Whittaker; Tom Shand (Coastal Engineering, 2025)

Inshore and offshore marine migration pathways of Atlantic salmon post‐smolts from multiple rivers in Scotland, England, Northern Ireland, and Ireland - Jessica R. Rodger; Jessie Lilly; Hannele M. Honkanen; Diego del Villar; Richard Kennedy; Niall Ó. Maoiléidigh; Patrick Boylan; Robert Rosell; David J. Morris; Ross O'Neill; Catherine Waters; Deirdre Cotter; et al. (Journal of Fish Biology, 2025)
The migratory behavior of Atlantic salmon ( Salmo salar ) post‐smolts in coastal waters is poorly understood. In this collaborative study, 1914 smolts, from 25 rivers, in four countries were tagged with acoustic transmitters during a single seasonal migration. In total, 1105 post‐smolts entered the marine study areas and 438 (39.6%) were detected on a network of 414 marine acoustic receivers and an autonomous underwater vehicle. Migration pathways (defined as the shortest distance between two detections) of up to 575 km and over 100 days at sea were described for all 25 populations. Post‐smolts from different rivers, as well as individuals from the same river, used different pathways in coastal waters. Although difficult to generalize to all rivers, at least during the year of this study, no tagged post‐smolts from rivers draining into the Irish Sea were detected entering the areas of sea between the Hebrides and mainland Scotland, which is associated with a high density of finfish aquaculture. An important outcome of this study is that a high proportion of post‐smolts crossed through multiple legislative jurisdictions and boundaries during their migration. This study provides the basis for spatially explicit assessment of the impact risk of coastal pressures on salmon during their first migration to sea.

‘Domesticability’: were some species predisposed for domestication? - Anne J. Romero; Anastasia Kolesnikova; Thomas H.G. Ezard; Michael Charles; Rafal M. Gutaker; Colin P. Osborne; Mark A. Chapman (Trends in Ecology & Evolution, 2025)

Limited persistence of the heat-tolerant zooxanthella, Durusdinium trenchii, in corals transplanted to a barrier reef where it is rare among natal colonies - Kira E. Turnham; Allison M. Lewis; Dustin W. Kemp; Mark E. Warner; Drew F. Wham; Robin T. Smith; Kenneth Hoadley; Patrick L. Colin; Yimnang Golbuu; Todd C. LaJeunesse (Coral Reefs, 2025)

Quaternary rivers, tufas and mires of southern England: Description of Geological Conservation Review sites - Rebecca M. Briant; Colin A. Whiteman; B. Andrew Haggart; David R. Bridgland; Ella Egberts; Michael J. Grant; Marcus Hatch; Peter G. Knowles; Danielle C. Schreve; Philip S. Toms; Francis F. Wenban-Smith; Mark J. White (Proceedings of the Geologists' Association, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Grazing impacts on experimentally restored aquatic macrophytes as critical habitat for the threatened Australian lungfish - Colin L. Burke; Luke Carpenter-Bundhoo; David T. Roberts; César Herrera; Hannah M. Franklin; Mark J. Kennard (Journal of Environmental Management, 2024)

Phenology Across Scales: An Intercontinental Analysis of Leaf‐Out Dates in Temperate Deciduous Tree Communities - Nicolas Delpierre; Suzon Garnier; Hugo Treuil‐Dussouet; Koen Hufkens; Jianhong Lin; Colin Beier; Michael Bell; Daniel Berveiller; Matthias Cuntz; Giulio Curioni; Kyla Dahlin; Sander O. Denham; et al. (Global Ecology and Biogeography, 2024)
Aim To quantify the intra‐community variability of leaf‐out (ICVLo) among dominant trees in temperate deciduous forests, assess its links with specific and phylogenetic diversity, identify its environmental drivers and deduce its ecological consequences with regard to radiation received and exposure to late frost. Location Eastern North America (ENA) and Europe (EUR). Time Period 2009–2022. Major Taxa Studied Temperate deciduous forest trees. Methods We developed an approach to quantify ICVLo through the analysis of RGB images taken from phenological cameras. We related ICVLo to species richness, phylogenetic diversity and environmental conditions. We quantified the intra‐community variability of the amount of radiation received and of exposure to late frost. Results Leaf‐out occurred over a longer time interval in ENA than in EUR. The sensitivity of leaf‐out to temperature was identical in both regions (−3.4 days per °C). The distributions of ICVLo were similar in EUR and ENA forests, despite the latter being more species‐rich and phylogenetically diverse. In both regions, cooler conditions and an earlier occurrence of leaf‐out resulted in higher ICVLo. ICVLo resulted in ca. 8% difference of radiation received from leaf‐out to September among individual trees. Forest communities in ENA had shorter safety margins as regards the exposure to late frosts, and were actually more frequently exposed to late frosts. Main Conclusions We conducted the first intercontinental analysis of the variability of leaf‐out at the scale of tree communities. North American and European forests showed similar ICVLo, in spite of their differences in terms of species richness and phylogenetic diversity, highlighting the relevance of environmental controls on ICVLo. We quantified two ecological implications of ICVLo (difference in terms of radiation received and exposure to late frost), which should be explored in the context of ongoing climate change, which affects trees differently according to their phenological niche.

An island of receptor-like genes at the Rrs13 locus on barley chromosome 6HS co-locate with three novel sources of scald resistance - Peter E. Eckstein; Lindsay J. Griffith; Xiang M. Zhang; T. Kelly Turkington; Mark G. Colin; Samuel Holden; Sean Walkowiak; Gurcharn S. Brar; Aaron D. Beattie (Theoretical and Applied Genetics, 2024)

Dynamics of microbiome and resistome in a poultry burger processing line - Natalia Merino; Elisa Pagán; Daniel Berdejo; Colin J. Worby; Mark Young; Abigail L. Manson; Rafael Pagán; Ashlee M. Earl; Diego García-Gonzalo (Food Research International, 2024)

Examining the sensitivity of ozone to NOx and VOCs in the Salt Lake City urban region from spatiotemporal patterns observed using stationary and mobile observations collected from a light-rail public transit platform - Andres Gonzalez; Derek Mallia; John C. Lin; Logan Mitchell; Taylor Y. Wilmot; Nancy Daher; Mark Sghiatti; Colin Harkins (Atmospheric Environment, 2024)

Investigating nuisance dust complaints: Combining high frequency dust deposition records and source identification using integrated microanalytical techniques - Kathryn L. Linge; Kari Pitts; Silvia Black; Angela Downey; Mark Brand; Peter Taylor; Colin Priddis (Atmospheric Pollution Research, 2024)

Palaeontological signatures of the Anthropocene are distinct from those of previous epochs - Mark Williams; Jan Zalasiewicz; Anthony D. Barnosky; Reinhold Leinfelder; Martin J. Head; Colin N. Waters; Francine M.G. McCarthy; Alejandro Cearreta; David C. Aldridge; Mary McGann; Paul B. Hamilton; Colin P. Summerhayes; et al. (Earth-Science Reviews, 2024)

Correction: On the Relationship Between Aquatic CO2 Concentration and Ecosystem Fluxes in Some of the World’s Key Wetland Types - Jessica L. Richardson; Ankur R. Desai; Jonathan Thom; Kim Lindgren; Hjalmar Laudon; Matthias Peichl; Mats Nilsson; Audrey Campeau; Järvi Järveoja; Peter Hawman; Deepak R. Mishra; Dontrece Smith; et al. (Wetlands, 2024)

Should I stay or should I go? The influence of environmental conditions on green turtle residence time and outward transit in foraging areas - Emily G. Webster; Stephanie Duce; Mark Hamann; Nicholas Murray; Takahiro Shimada; Colin Limpus (Marine Biology, 2024)
Foraging animals move through the environment to satisfy their requirements for food, rest, reproduction and risk-avoidance. Understanding how animals respond to changing environmental conditions can help to characterise favourable habitat and determine whether they might be motivated to depart when those habitats become unsuitable. Foraging green turtles are typically residents that scarcely move in response to environmental changes or disturbances. Some individuals though, exhibit high mobility at fine scales. We developed an analysis of Fastloc GPS tracks of 61 green turtles using cox regression models and generalised linear mixed models to investigate the influence of a suite of environmental characteristics on the length of residence time and probability of turtles transitioning between two behavioural modes, “stay” or “go”. Decisions to move (“go”) were influenced by short-term changes in the local environmental conditions. Individuals were more likely to “stay” when temperature increased during their stay and were more likely to “go” when turbidity decreased, and they entered deeper habitats. This result implies that foraging and resting (“staying”) primarily occurs in benthic, shallow, warm habitats, while transit (“going”) is facilitated in deeper, clear water. We also determined that individuals within the green turtle foraging aggregation respond differently to environmental cues to move and hypothesise that a diversity of strategies within a foraging aggregation could confer its resilience to disturbance events. Our study provides new evidence of the factors influencing movements in green turtles and can aid in predicting how they may respond to future changes and enhance risk mitigation efforts through dynamic and adaptive planning.

Earthworm lipid content and size help account for differences in pesticide bioconcentration between species - Jun Li; Mark E. Hodson; Colin D. Brown; Melanie J. Bottoms; Roman Ashauer; Tania Alvarez (Journal of Hazardous Materials, 2024)

Molecular mechanisms underlying NLRP3 inflammasome activation and IL-1β production in air pollution fine particulate matter (PM2.5)-primed macrophages - Lourdes Caceres; Tijani Abogunloko; Sara Malchow; Fabienne Ehret; Julian Merz; Xiaowei Li; Lucia Sol Mitre; Natalia Magnani; Deborah Tasat; Timothy Mwinyella; Lisa Spiga; Dymphie Suchanek; et al. (Environmental Pollution, 2024)

On the Relationship Between Aquatic CO2 Concentration and Ecosystem Fluxes in Some of the World’s Key Wetland Types - Jessica L. Richardson; Ankur R. Desai; Jonathan Thom; Kim Lindgren; Hjalmar Laudon; Matthias Peichl; Mats Nilsson; Audrey Campeau; Järvi Järveoja; Peter Hawman; Deepak R. Mishra; Dontrece Smith; et al. (Wetlands, 2024)

Persistent net release of carbon dioxide and methane from an Alaskan lowland boreal peatland complex - Eugénie S. Euskirchen; Colin W. Edgar; Evan S. Kane; Mark P. Waldrop; Rebecca B. Neumann; Kristen L. Manies; Thomas A. Douglas; Catherine Dieleman; Miriam C. Jones; Merritt R. Turetsky (Global Change Biology, 2024)
Permafrost degradation in peatlands is altering vegetation and soil properties and impacting net carbon storage. We studied four adjacent sites in Alaska with varied permafrost regimes, including a black spruce forest on a peat plateau with permafrost, two collapse scar bogs of different ages formed following thermokarst, and a rich fen without permafrost. Measurements included year‐round eddy covariance estimates of net carbon dioxide (CO 2 ), mid‐April to October methane (CH 4 ) emissions, and environmental variables. From 2011 to 2022, annual rainfall was above the historical average, snow water equivalent increased, and snow‐season duration shortened due to later snow return. Seasonally thawed active layer depths also increased. During this period, all ecosystems acted as slight annual sources of CO 2 (13–59 g C m −2 year −1 ) and stronger sources of CH 4 (11–14 g CH 4 m −2 from ~April to October). The interannual variability of net ecosystem exchange was high, approximately ±100 g C m −2 year −1 , or twice what has been previously reported across other boreal sites. Net CO 2 release was positively related to increased summer rainfall and winter snow water equivalent and later snow return. Controls over CH 4 emissions were related to increased soil moisture and inundation status. The dominant emitter of carbon was the rich fen, which, in addition to being a source of CO 2 , was also the largest CH 4 emitter. These results suggest that the future carbon‐source strength of boreal lowlands in Interior Alaska may be determined by the area occupied by minerotrophic fens, which are expected to become more abundant as permafrost thaw increases hydrologic connectivity. Since our measurements occur within close proximity of each other (≤1 km 2 ), this study also has implications for the spatial scale and data used in benchmarking carbon cycle models and emphasizes the necessity of long‐term measurements to identify carbon cycle process changes in a warming climate.

Identification and quantification of Acanthamoeba spp. within seawater at four coastal lagoons on the east coast of Australia - Binod Rayamajhee; Nathan L.R. Williams; Nachshon Siboni; Kiri Rodgers; Mark Willcox; Fiona L. Henriquez; Justin R. Seymour; Jaimie Potts; Colin Johnson; Peter Scanes; Nicole Carnt (Science of The Total Environment, 2023)

The Anthropocene as an epoch is distinct from all other concepts known by this term: a reply to Swindles et al. (2023) - Martin J. Head; Colin N. Waters; Jan A. Zalasiewicz; Anthony D. Barnosky; Simon D. Turner; Alejandro Cearreta; Reinhold Leinfelder; Francine M.G. McCarthy; Daniel de B. Richter; Neil L. Rose; Yoshiki Saito; Davor Vidas; et al. (Journal of Quaternary Science, 2023)

Exploring the potential effect of phospholipase A2 antibody to extend beef shelf-life in a beef liposome model system - Colin K.Y. Chun; Mary Roth; Ruth Welti; Mark P. Richards; Wei-Wen Hsu; Travis O'Quinn; Michael D. Chao (Meat Science, 2023)

Projecting COVID-19 cases and hospital burden in Ohio - Wasiur R. KhudaBukhsh; Caleb Deen Bastian; Matthew Wascher; Colin Klaus; Saumya Yashmohini Sahai; Mark H. Weir; Eben Kenah; Elisabeth Root; Joseph H. Tien; Grzegorz A. Rempała (Journal of Theoretical Biology, 2023)

Response to Merritts et al. (2023): The Anthropocene is complex. Defining it is not - Colin N. Waters; Martin J. Head; Jan Zalasiewicz; Francine M.G. McCarthy; Scott L. Wing; Peter K. Haff; Mark Williams; Anthony D. Barnosky; Barbara Fiałkiewicz-Kozieł; Reinhold Leinfelder; J.R. McNeill; Neil L. Rose; et al. (Earth-Science Reviews, 2023)

Testing whether reducing brown trout biomass in peatland lakes increases macro-invertebrate biomass and invertivorous waterbird occurrence - Mark H. Hancock; Daniela Klein; Robert Hughes; Paul Stagg; Paul Byrne; Trevor D. Smith; Alison MacLennan; Paul P. J. Gaffney; Colin W. Bean (Aquatic Ecology, 2023)

Vulnerability to climate change of managed stocks in the California Current large marine ecosystem - Michelle M. McClure; Melissa A. Haltuch; Ellen Willis-Norton; David D. Huff; Elliott L. Hazen; Lisa G. Crozier; Michael G. Jacox; Mark W. Nelson; Kelly S. Andrews; Lewis A.K. Barnett; Aaron M. Berger; Sabrina Beyer; et al. (Frontiers in Marine Science, 2023)
Introduction Understanding how abundance, productivity and distribution of individual species may respond to climate change is a critical first step towards anticipating alterations in marine ecosystem structure and function, as well as developing strategies to adapt to the full range of potential changes. Methods This study applies the NOAA (National Oceanic and Atmospheric Administration) Fisheries Climate Vulnerability Assessment method to 64 federally-managed species in the California Current Large Marine Ecosystem to assess their vulnerability to climate change, where vulnerability is a function of a species’ exposure to environmental change and its biological sensitivity to a set of environmental conditions, which includes components of its resiliency and adaptive capacity to respond to these new conditions. Results Overall, two-thirds of the species were judged to have Moderate or greater vulnerability to climate change, and only one species was anticipated to have a positive response. Species classified as Highly or Very Highly vulnerable share one or more characteristics including: 1) having complex life histories that utilize a wide range of freshwater and marine habitats; 2) having habitat specialization, particularly for areas that are likely to experience increased hypoxia; 3) having long lifespans and low population growth rates; and/or 4) being of high commercial value combined with impacts from non-climate stressors such as anthropogenic habitat degradation. Species with Low or Moderate vulnerability are either habitat generalists, occupy deep-water habitats or are highly mobile and likely to shift their ranges. Discussion As climate-related changes intensify, this work provides key information for both scientists and managers as they address the long-term sustainability of fisheries in the region. This information can inform near-term advice for prioritizing species-level data collection and research on climate impacts, help managers to determine when and where a precautionary approach might be warranted, in harvest or other management decisions, and help identify habitats or life history stages that might be especially effective to protect or restore.

A Meta-Analysis of the Genome-Wide Association Studies on Two Genetically Correlated Phenotypes Suggests Four New Risk Loci for Headaches - Weihua Meng; Parminder S. Reel; Charvi Nangia; Aravind Lathika Rajendrakumar; Harry L. Hebert; Qian Guo; Mark J. Adams; Hua Zheng; Zen Haut Lu; Debashree Ray; Lesley A. Colvin; Colin N. A. Palmer; et al. (Phenomics, 2023)
Headache is one of the commonest complaints that doctors need to address in clinical settings. The genetic mechanisms of different types of headache are not well understood while it has been suggested that self-reported headache and self-reported migraine were genetically correlated. In this study, we performed a meta-analysis of genome-wide association studies (GWAS) on the self-reported headache phenotype from the UK Biobank and the self-reported migraine phenotype from the 23andMe using the Unified Score-based Association Test (metaUSAT) software for genetically correlated phenotypes ( N = 397,385). We identified 38 loci for headaches, of which 34 loci have been reported before and four loci were newly suggested. The LDL receptor related protein 1 ( LRP1 )— Signal Transducer and Activator of Transcription 6 ( STAT6 )— S hort chain D ehydrogenase / R eductase family 9C member 7 ( SDR9C7 ) region in chromosome 12 was the most significantly associated locus with a leading p value of 1.24 × 10 –62 of rs11172113. The One Cut homeobox 2 ( ONECUT2 ) gene locus in chromosome 18 was the strongest signal among the four new loci with a p value of 1.29 × 10 –9 of rs673939. Our study demonstrated that the genetically correlated phenotypes of self-reported headache and self-reported migraine can be meta-analysed together in theory and in practice to boost study power to identify more variants for headaches. This study has paved way for a large GWAS meta-analysis involving cohorts of different while genetically correlated headache phenotypes.

Characterization of the molecular mechanisms of silicon uptake in coccolithophores - Sarah Ratcliffe; Erin M. Meyer; Charlotte E. Walker; Michael Knight; Heather M. McNair; Paul G. Matson; Debora Iglesias‐Rodriguez; Mark Brzezinski; Gerald Langer; Aleksey Sadekov; Mervyn Greaves; Colin Brownlee; et al. (Environmental Microbiology, 2023)
Coccolithophores are an important group of calcifying marine phytoplankton. Although coccolithophores are not silicified, some species exhibit a requirement for Si in the calcification process. These species also possess a novel protein (SITL) that resembles the SIT family of Si transporters found in diatoms. However, the nature of Si transport in coccolithophores is not yet known, making it difficult to determine the wider role of Si in coccolithophore biology. Here, we show that coccolithophore SITLs act as Na + ‐coupled Si transporters when expressed in heterologous systems and exhibit similar characteristics to diatom SITs. We find that CbSITL from Coccolithus braarudii is transcriptionally regulated by Si availability and is expressed in environmental coccolithophore populations. However, the Si requirement of C. braarudii and other coccolithophores is very low, with transport rates of exogenous Si below the level of detection in sensitive assays of Si transport. As coccoliths contain only low levels of Si, we propose that Si acts to support the calcification process, rather than forming a structural component of the coccolith itself. Si is therefore acting as a micronutrient in coccolithophores and natural populations are only likely to experience Si limitation in circumstances where dissolved silicon (DSi) is depleted to extreme levels.

Conceptual frameworks and key questions for assessing the contribution of marine protected areas to shark and ray conservation - Andrew Chin; Fergus John Molloy; Darren Cameron; Jon C. Day; Jessica Cramp; Karin Leeann Gerhardt; Michelle R. Heupel; Mark Read; Colin A. Simpfendorfer (Conservation Biology, 2023)
Marine protected areas (MPAs) are key tools in addressing the global decline of sharks and rays, and marine parks and shark sanctuaries of various configurations have been established to conserve shark populations. However, assessments of their efficacy are compromised by inconsistent terminology, lack of standardized approaches to assess how MPAs contribute to shark and ray conservation, and ambiguity about how to integrate movement data in assessment processes. We devised a conceptual framework to standardize key terms (e.g., protection , contribution , potential impact , risk , threat ) and used the concept of portfolio risk to identify key attributes of sharks and rays (assets), the threats they face (portfolio risk), and the specific role of MPAs in risk mitigation (insurance). Movement data can be integrated into the process by informing risk exposure and mitigation through MPAs. The framework is operationalized by posing 8 key questions that prompt practitioners to consider the assessment scope, MPA type and purpose, range of existing and potential threats, species biology and ecology, and management and operational contexts. Ultimately, MPA contributions to shark and ray conservation differ according to a complex set of human and natural factors and interactions that should be carefully considered in MPA design, implementation, and evaluation.

Downstream Modification of Mercury in Diverse River Systems Underscores the Role of Local Conditions in Fish Bioaccumulation - Craig A. Emmerton; Paul E. Drevnick; Jessica A. Serbu; Colin A. Cooke; Jennifer A. Graydon; Megan Reichert; Marlene S. Evans; Mark E. McMaster (Ecosystems, 2023)
Fish consumption advisories for mercury (Hg) are common in rivers, highlighting connections between landscape sources of Hg and downstream fluvial ecosystems. Though watershed conditions can influence concentrations of Hg in smaller streams, how Hg changes downstream through larger rivers and how these changes associate with Hg concentrations in fish is not well understood. Here we present a continuum of concentrations and yields of total mercury (THg) and methylmercury (MeHg) from small tributary systems draining diverse western Canadian headwater landscapes through to major transboundary rivers. We associate these downstream patterns with THg concentrations in tissues of resident fish in major rivers. Mean concentrations and yields of unfiltered THg from over 80 monitored tributaries and major rivers were highly variable in space ranging from 0.28 to 120 ng L −1 and 0.39 to 170 µg ha −1 d −1 , respectively. Using spatial data and a hierarchical cluster analysis, we identified three broad categories of tributary catchment conditions. Linear mixed modeling analysis with water quality variables revealed significantly lower THg concentrations in tributaries draining cordillera-foothills (geometric mean: 0.76 ng L −1 ) regions relative to those draining forested (1.5 ng L −1 ) and agriculturalized landscapes (2.4 ng L −1 ), suggesting that sources and mobility of THg in soils and surface waters were different between landscapes. However, these concentration differences were not sustained downstream in major rivers as local sources and sinks of THg in river channels smoothed differences between landscape types. Extensive fish tissue monitoring in major rivers and ANCOVA analysis found that site-specific, river water THg and MeHg concentrations and local catchment conditions were stronger associates of THg concentrations in fish than broader trends in rivers within and across landscape classes. Consequently, site-specific, targeted monitoring of THg and MeHg concentrations in water and fish is a preferred study design when assessing regional-level patterns in fish tissue concentrations.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Consensus Head Acceleration Measurement Practices (CHAMP): Laboratory Validation of Wearable Head Kinematic Devices - Lee Gabler; Declan Patton; Mark Begonia; Ray Daniel; Ahmad Rezaei; Colin Huber; Gunter Siegmund; Tyler Rooks; Lyndia Wu (Annals of Biomedical Engineering, 2022)
Wearable devices are increasingly used to measure real-world head impacts and study brain injury mechanisms. These devices must undergo validation testing to ensure they provide reliable and accurate information for head impact sensing, and controlled laboratory testing should be the first step of validation. Past validation studies have applied varying methodologies, and some devices have been deployed for on-field use without validation. This paper presents best practices recommendations for validating wearable head kinematic devices in the laboratory, with the goal of standardizing validation test methods and data reporting. Key considerations, recommended approaches, and specific considerations were developed for four main aspects of laboratory validation, including surrogate selection, test conditions, data collection, and data analysis. Recommendations were generated by a group with expertise in head kinematic sensing and laboratory validation methods and reviewed by a larger group to achieve consensus on best practices. We recommend that these best practices are followed by manufacturers, users, and reviewers to conduct and/or review laboratory validation of wearable devices, which is a minimum initial step prior to on-field validation and deployment. We anticipate that the best practices recommendations will lead to more rigorous validation of wearable head kinematic devices and higher accuracy in head impact data, which can subsequently advance brain injury research and management.

The proposed Anthropocene Epoch/Series is underpinned by an extensive array of mid‐20 th century stratigraphic event signals - Martin J. Head; Jan A. Zalasiewicz; Colin N. Waters; Simon D. Turner; Mark Williams; Anthony D. Barnosky; Will Steffen; Michael Wagreich; Peter K. Haff; Jaia Syvitski; Reinhold Leinfelder; Francine M. G. Mccarthy; et al. (Journal of Quaternary Science, 2022)
The extensive array of mid‐20 th century stratigraphic event signals associated with the ‘Great Acceleration’ enables precise and unambiguous recognition of the Anthropocene as an epoch/series within the Geological Time Scale. A mid‐20 th century inception is consistent with Earth System science analysis in which the Anthropocene term and concept arose, and would reflect the reality that our planet has sharply exited the range of natural variability characterizing the Holocene Epoch/Series, which the Anthropocene would therefore terminate. An alternative, recently proposed ‘geological event’ approach to the Anthropocene is primarily an interdisciplinary concept, encompassing historical and socio‐cultural processes and their global environmental impacts over a diachronous timeframe that extends back at least many millennia. Resembling more closely a geological episode than an event , it would decouple the Anthropocene from its chronostratigraphic delineation and association with an abrupt planetary perturbation; but separately defined and differently named it might be usefully complementary. We recommend a clear separation of epochs , events and episodes . An epoch is a formal subdivision of the Geological Time Scale, and its correlation may be assisted by one or more events ; an event is usually, and particularly in the Quaternary, a brief incident or perturbation with a sedimentary expression; and an episode is a longer, internally complex time interval that may include several events and even extend across several epochs.

An integrated approach to assessing abiotic and biotic threats to post‐fire plant species recovery: Lessons from the 2019–2020 Australian fire season - Rachael V. Gallagher; Stuart P. Allen; Berin D. E. Mackenzie; David A. Keith; Rachael H. Nolan; Libby Rumpff; Carl R. Gosper; Geoffrey Pegg; Stephen van Leeuwen; Mark K. J. Ooi; Colin J. Yates; Cory Merow; et al. (Global Ecology and Biogeography, 2022)
Aim Existing abiotic and biotic threats to plant species (e.g., disease, drought, invasive species) affect their capacity to recover post‐fire. We use a new, globally applicable framework to assess the vulnerability of 26,062 Australian plant species to a suite of active threats after the 2019–2020 fires. Location Australia. Time period 2019–2020. Major species studied Plants. Methods Spatial data for existing threats and information on species‐level susceptibility were combined with estimates of the extent of range burnt in southern Australia (> 22°S) to assign species against 10 criteria into vulnerability categories ( high , medium , low , none , data deficient ). We explore in detail results for three threats (drought, disease, feral animals), highlighting where impacts from multiple threats ranked high vulnerability may compound to reduce post‐fire recovery. Results Analysis of the full suite of 10 vulnerability criteria, which encompass a broad range of threats, revealed large numbers of species vulnerable to poor post‐fire recovery from one or more different hazards ( high vulnerability: 1,243 species; medium vulnerability: 2,450 species). Collectively, 457 plant species that burnt extensively (> 50%) across their range are highly vulnerable to poor recovery due to exposure to pre‐fire drought conditions (235 species), disease (186 species), or feral animals (97 species). Of these 457 species, 61 are vulnerable to more than one of these three threats, highlighting how a suite of interacting hazards can impact plant recovery after fire. Main conclusions While fire can renew plant populations by stimulating recruitment and resetting competitive interactions, the presence of existing threats in post‐fire landscapes jeopardizes recovery. The simultaneous impact of multiple threats that impact recovery can create a suite of hazards that contribute to declines and, potentially, extinction. Our method for rapid post‐fire vulnerability assessment can be applied to large numbers of plant species or other biota in fire affected regions globally.

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

Scientists Against War: A Plea to World Leaders for Better Governance - Seithikurippu R. Pandi-Perumal; Velayudhan Mohan Kumar; Namasivayam Ganesh Pandian; Joop T. de Jong; Sudalaikannu Andiappan; Alexandru Corlateanu; Arehally Marappa Mahalaksmi; Saravana Babu Chidambaram; Ramasamy Rajesh Kumar; Chellamuthu Ramasubramanian; Sudhakar Sivasubramaniam; Alvhild Alette Bjørkum; et al. (Sleep and Vigilance, 2022)

Satellite tagging and flipper tag recoveries reveal migration patterns and foraging distribution of loggerhead sea turtles (Caretta caretta) from eastern Australia - Michelle A. Perez; Colin J. Limpus; Kate Hofmeister; Takahiro Shimada; Aub Strydom; Emily Webster; Mark Hamann (Marine Biology, 2022)
Marine turtles encounter different threats during various life-history stages. Therefore, understanding their movements and spatial distribution is crucial for effectively managing these long-lived migratory organisms. This study combines satellite telemetry data with long-term capture-mark-recapture data derived from flipper tag studies to determine distribution patterns of endangered loggerhead turtles ( Caretta caretta ) during post-nesting migrations from different eastern Australian nesting sites. Individuals from the K’gari-Fraser Island and Great Barrier Reef island rookeries typically migrated northward, whereas individuals from mainland rookeries migrated equally northward and southward. Despite this difference in foraging distribution, loggerheads from the different rookeries did not differ substantially in their migration duration or distance travelled. The foraging distribution identified from successful satellite tag deployments represented 50% of the foraging distribution identified from a large long-term flipper tag recovery database. However, these satellite telemetry results have identified new migration and foraging habitats not previously recognised for loggerhead turtles nesting in eastern Australia. Additionally, they support the conclusion from a past study using flipper tag recovery data that the mainland nesting turtles migrate to different foraging grounds than the turtles nesting on Great Barrier Reef islands. Collectively, the two data sources provide valuable data on the migration route, habitat distribution and ecological range for a threatened genetic stock of loggerhead turtles.

Flukebook: an open-source AI platform for cetacean photo identification - Drew Blount; Shane Gero; Jon Van Oast; Jason Parham; Colin Kingen; Ben Scheiner; Tanya Stere; Mark Fisher; Gianna Minton; Christin Khan; Violaine Dulau; Jaime Thompson; et al. (Mammalian Biology, 2022)
Determining which species are at greatest risk, where they are most vulnerable, and what are the trajectories of their communities and populations is critical for conservation and management. Globally distributed, wide-ranging whales and dolphins present a particular challenge in data collection because no single research team can record data over biologically meaningful areas. Flukebook.org is an open-source web platform that addresses these gaps by providing researchers with the latest computational tools. It integrates photo-identification algorithms with data management, sharing, and privacy infrastructure for whale and dolphin research, enabling the global collaborative study of these global species. With seven automatic identification algorithms trained for 15 different species, resulting in 37 species-specific identification pipelines, Flukebook is an extensible foundation that continually incorporates emerging AI techniques and applies them to cetacean photo identification through continued collaboration between computer vision researchers, software engineers, and biologists. With over 2.0 million photos of over 52,000 identified individual animals submitted by over 250 researchers, the platform enables a comprehensive understanding of cetacean populations, fostering international and cross-institutional collaboration while respecting data ownership and privacy. We outline the technology stack and architecture of Flukebook, its performance on real-world cetacean imagery, and its development as an example of scalable, extensible, and reusable open-source conservation software. Flukebook is a step change in our ability to conduct large-scale research on cetaceans across biologically meaningful geographic ranges, to rapidly iterate population assessments and abundance trajectories, and engage the public in actions to protect them.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Continental‐scale acoustic telemetry and network analysis reveal new insights into stock structure - Elodie J. I. Lédée; Michelle R. Heupel; Matthew D. Taylor; Robert G. Harcourt; Fabrice R. A. Jaine; Charlie Huveneers; Vinay Udyawer; Hamish A. Campbell; Russell C. Babcock; Xavier Hoenner; Adam Barnett; Matias Braccini; et al. (Fish and Fisheries, 2021)
Delineation of population structure (i.e. stocks) is crucial to successfully manage exploited species and to address conservation concerns for threatened species. Fish migration and associated movements are key mechanisms through which discrete populations mix and are thus important determinants of population structure. Detailed information on fish migration and movements is becoming more accessible through advances in telemetry and analysis methods however such information is not yet used systematically in stock structure assessment. Here, we described how detections of acoustically tagged fish across a continental‐scale array of underwater acoustic receivers were used to assess stock structure and connectivity in seven teleost and seven shark species and compared to findings from genetic and conventional tagging. Network analysis revealed previously unknown population connections in some species, and in others bolstered support for existing stock discrimination by identifying nodes and routes important for connectivity. Species with less variability in their movements required smaller sample sizes (45–50 individuals) to reveal useful stock structure information. Our study shows the power of continental‐scale acoustic telemetry networks to detect movements among fishery jurisdictions. We highlight methodological issues that need to be considered in the design of acoustic telemetry studies for investigating stock structure and the interpretation of the resulting data. The advent of broad‐scale acoustic telemetry networks across the globe provides new avenues to understand how movement informs population structure and can lead to improved management.

New Constraints on the Physical and Biological Controls on the Silicon Isotopic Composition of the Arctic Ocean - Mark A. Brzezinski; Ivia Closset; Janice L. Jones; Gregory F. de Souza; Colin Maden (Frontiers in Marine Science, 2021)
The silicon isotope composition of silicic acid, δ 30 Si(OH) 4 , in the deep Arctic Ocean is anomalously heavy compared to all other deep ocean basins. To further evaluate the mechanisms leading to this condition, δ 30 Si(OH) 4 was examined on US GEOTRACES section GN01 from the Bering Strait to the North Pole. Isotope values in the polar mixed layer showed a strong influence of the transpolar drift. Drift waters contained relatively high [Si(OH) 4 ] with heavy δ 30 Si(OH) 4 consistent with the high silicate of riverine source waters and strong biological Si(OH) 4 consumption on the Eurasian shelves. The maximum in silicic acid concentration, [Si(OH) 4 ], within the double halocline of the Canada Basin formed a local minimum in δ 30 Si(OH) 4 that extended across the Canada Basin, reflecting the high-[Si(OH) 4 ] Pacific source waters and benthic inputs of Si(OH) 4 in the Chukchi Sea. δ 30 Si(OH) 4 became lighter with the increase in [Si(OH) 4 ] in intermediate and deep waters; however, both Canada Basin deep water and Eurasian Basin deep water were heavier than deep waters from other ocean basins. A preliminary isotope budget incorporating all available Arctic δ 30 Si(OH) 4 data confirms the importance of isotopically heavy inflows in creating the anomalous deep Arctic Si isotope signature, but also reveals a surprising similarity in the isotopic composition of the major inflows compared to outflows across the main gateways connecting the Arctic with the Pacific and the Atlantic. This similarity implies a major role of biological productivity and opal burial in removing light isotopes entering the Arctic Ocean from rivers.

Plastic Pollution and Small Juvenile Marine Turtles: A Potential Evolutionary Trap - Emily M. Duncan; Annette C. Broderick; Kay Critchell; Tamara S. Galloway; Mark Hamann; Colin J. Limpus; Penelope K. Lindeque; David Santillo; Anton D. Tucker; Scott Whiting; Erina J. Young; Brendan J. Godley (Frontiers in Marine Science, 2021)
The ingestion of plastic by marine turtles is now reported for all species. Small juvenile turtles (including post-hatchling and oceanic juveniles) are thought to be most at risk, due to feeding preferences and overlap with areas of high plastic abundance. Their remote and dispersed life stage, however, results in limited access and assessments. Here, stranded and bycaught specimens from Queensland Australia, Pacific Ocean (PO; n = 65; 1993–2019) and Western Australia, Indian Ocean (IO; n = 56; 2015–2019) provide a unique opportunity to assess the extent of plastic (> 1mm) ingestion in five species [green ( Chelonia mydas ), loggerhead ( Caretta caretta ), hawksbill ( Eretmochelys imbricata ), olive ridley ( Lepidochelys olivacea ), and flatback turtles ( Natator depressus )]. In the Pacific Ocean, high incidence of ingestion occurred in green (83%; n = 36), loggerhead (86%; n = 7), flatback (80%; n = 10) and olive ridley turtles (29%; n = 7). There was an overall lower incidence in IO; highest being in the flatback (28%; n = 18), the loggerhead (21%; n = 14) and green (9%; n = 22). No macroplastic debris ingestion was documented for hawksbill turtles in either site although sample sizes were smaller for this species (PO n = 5; IO n = 2). In the Pacific Ocean, the majority of ingested debris was made up of hard fragments (mean of all species 52%; species averages 46–97%), whereas for the Indian Ocean these were filamentous plastics (52%; 43–77%). The most abundant colour for both sites across all species was clear (PO: 36%; IO: 39%), followed by white for PO (36%) then green and blue for IO (16%; 16%). The polymers most commonly ingested by turtles in both oceans were polyethylene (PE; PO-58%; IO-39%) and polypropylene (PP; PO-20.2%; IO-23.5%). We frame the high occurrence of ingested plastic present in this marine turtle life stage as a potential evolutionary trap as they undertake their development in what are now some of the most polluted areas of the global oceans.

Exploring controls of the early and stepped deglaciation on the western margin of the British Irish Ice Sheet - Sara Benetti; Richard C. Chiverrell; Colm Ó Cofaigh; Matt Burke; Alicia Medialdea; David Small; Colin Ballantyne; Mark D. Bateman; S. Louise Callard; Peter Wilson; Derek Fabel; Chris D. Clark; et al. (Journal of Quaternary Science, 2021)
New optically stimulated luminescence dating and Bayesian models integrating all legacy and BRITICE‐CHRONO geochronology facilitated exploration of the controls on the deglaciation of two former sectors of the British–Irish Ice Sheet, the Donegal Bay (DBIS) and Malin Sea ice‐streams (MSIS). Shelf‐edge glaciation occurred ~27 ka, before the global Last Glacial Maximum, and shelf‐wide retreat began 26–26.5 ka at a rate of ~18.7–20.7 m a –1 . MSIS grounding zone wedges and DBIS recessional moraines show episodic retreat punctuated by prolonged still‐stands. By ~23–22 ka the outer shelf (~25 000 km 2 ) was free of grounded ice. After this time, MSIS retreat was faster (~20 m a –1 vs. ~2–6 m a –1 of DBIS). Separation of Irish and Scottish ice sources occurred ~20–19.5 ka, leaving an autonomous Donegal ice dome. Inner Malin shelf deglaciation followed the submarine troughs reaching the Hebridean coast ~19 ka. DBIS retreat formed the extensive complex of moraines in outer Donegal Bay at 20.5–19 ka. DBIS retreated on land by ~17–16 ka. Isolated ice caps in Scotland and Ireland persisted until ~14.5 ka. Early retreat of this marine‐terminating margin is best explained by local ice loading increasing water depths and promoting calving ice losses rather than by changes in global temperatures. Topographical controls governed the differences between the ice‐stream retreat from mid‐shelf to the coast.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Global transcriptomic profiles of circulating leucocytes in early lactation cows with clinical or subclinical mastitis - Zhangrui Cheng; Laura Buggiotti; Mazdak Salavati; Cinzia Marchitelli; Sergio Palma-Vera; Alistair Wylie; Haruko Takeda; Lijing Tang; Mark A. Crowe; D. Claire Wathes; Mark Crowe; Niamh McLoughlin; et al. (Molecular Biology Reports, 2021)

An agenda for ethics and justice in adaptation to climate change - Morten Fibieger Byskov; Keith Hyams; Poshendra Satyal; Isabelle Anguelovski; Lisa Benjamin; Sophie Blackburn; Maud Borie; Simon Caney; Eric Chu; Gareth Edwards; Kristel Fourie; Arabella Fraser; et al. (Climate and Development, 2021)

Identification of loci for pre-harvest sprouting resistance in the highly dormant spring wheat RL4137 - M. M. Uzzal A. Liton; Curt A. McCartney; Colin W. Hiebert; Santosh Kumar; Mark C. Jordan; Belay T. Ayele (Theoretical and Applied Genetics, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Preparing interdisciplinary leadership for a sustainable future - Christopher G. Boone; Steward T. A. Pickett; Gabriele Bammer; Kamal Bawa; Jennifer A. Dunne; Iain J. Gordon; David Hart; Jessica Hellmann; Alison Miller; Mark New; Jean P. Ometto; Ken Taylor; et al. (Sustainability Science, 2020)

Plant respiration: Controlled by photosynthesis or biomass? - Alessio Collalti; Mark G. Tjoelker; Günter Hoch; Annikki Mäkelä; Gabriele Guidolotti; Mary Heskel; Giai Petit; Michael G. Ryan; Giovanna Battipaglia; Giorgio Matteucci; Iain Colin Prentice (Global Change Biology, 2020)
Two simplifying hypotheses have been proposed for whole‐plant respiration. One links respiration to photosynthesis; the other to biomass. Using a first‐principles carbon balance model with a prescribed live woody biomass turnover, applied at a forest research site where multidecadal measurements are available for comparison, we show that if turnover is fast the accumulation of respiring biomass is low and respiration depends primarily on photosynthesis; while if turnover is slow the accumulation of respiring biomass is high and respiration depends primarily on biomass. But the first scenario is inconsistent with evidence for substantial carry‐over of fixed carbon between years, while the second implies far too great an increase in respiration during stand development—leading to depleted carbohydrate reserves and an unrealistically high mortality risk. These two mutually incompatible hypotheses are thus both incorrect. Respiration is not linearly related either to photosynthesis or to biomass, but it is more strongly controlled by recent photosynthates (and reserve availability) than by total biomass.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Tropical Western Pacific Thermal Structure and its Relationship to Ocean Surface Variables: A Numerical State Estimate and Forereef Temperature Records - Travis Schramek; Bruce Cornuelle; Ganesh Gopalakrishnan; Patrick Colin; Sonia Rowley; Mark Merrifield; Eric Terrill (Oceanography, 2019)

Energy and Momentum Lost to Wake Eddies and Lee Waves Generated by the North Equatorial Current and Tidal Flows at Peleliu, Palau - Shaun Johnston; Jennifer MacKinnon; Patrick Colin; Patrick Haley; Pierre Lermusiaux; Andrew Lucas; Mark Merrifield; Sophia Merrifield; Chris Mirabito; Jonathan Nash; Celia Ou; Mika Siegelman; et al. (Oceanography, 2019)

Island Wakes Observed from High-Frequency Current Mapping Radar - Sophia Merrifield; Patrick Colin; Thomas Cook; Carlos Garcia-Moreno; Jennifer MacKinnon; Mark Otero; Travis Schramek; Mika Siegelman; Harper Simmons; Eric Terrill (Oceanography, 2019)

Citizen science reveals female sand tiger sharks ( Carcharias taurus ) exhibit signs of site fidelity on shipwrecks - Avery B. Paxton; Erica Blair; Camryn Blawas; Michael H. Fatzinger; Madeline Marens; Jason Holmberg; Colin Kingen; Tanya Houppermans; Mark Keusenkothen; John McCord; Brian R. Silliman; Linda M. Penfold (Ecology, 2019)

Re-analysis of archaeobotanical remains from pre- and early agricultural sites provides no evidence for a narrowing of the wild plant food spectrum during the origins of agriculture in southwest Asia - Michael Wallace; Glynis Jones; Michael Charles; Emily Forster; Eleanor Stillman; Vincent Bonhomme; Alexandra Livarda; Colin P. Osborne; Mark Rees; Georg Frenck; Catherine Preece (Vegetation History and Archaeobotany, 2019)

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Microplastic ingestion ubiquitous in marine turtles - Emily M. Duncan; Annette C. Broderick; Wayne J. Fuller; Tamara S. Galloway; Matthew H. Godfrey; Mark Hamann; Colin J. Limpus; Penelope K. Lindeque; Andrew G. Mayes; Lucy C. M. Omeyer; David Santillo; Robin T. E. Snape; et al. (Global Change Biology, 2019)
Despite concerns regarding the environmental impacts of microplastics, knowledge of the incidence and levels of synthetic particles in large marine vertebrates is lacking. Here, we utilize an optimized enzymatic digestion methodology, previously developed for zooplankton, to explore whether synthetic particles could be isolated from marine turtle ingesta. We report the presence of synthetic particles in every turtle subjected to investigation ( n = 102) which included individuals from all seven species of marine turtle, sampled from three ocean basins (Atlantic [ATL]: n = 30, four species; Mediterranean (MED): n = 56, two species; Pacific (PAC): n = 16, five species). Most particles ( n = 811) were fibres (ATL: 77.1% MED: 85.3% PAC: 64.8%) with blue and black being the dominant colours. In lesser quantities were fragments (ATL: 22.9%: MED: 14.7% PAC: 20.2%) and microbeads (4.8%; PAC only; to our knowledge the first isolation of microbeads from marine megavertebrates). Fourier transform infrared spectroscopy (FT‐IR) of a subsample of particles ( n = 169) showed a range of synthetic materials such as elastomers (MED: 61.2%; PAC: 3.4%), thermoplastics (ATL: 36.8%: MED: 20.7% PAC: 27.7%) and synthetic regenerated cellulosic fibres (SRCF; ATL: 63.2%: MED: 5.8% PAC: 68.9%). Synthetic particles being isolated from species occupying different trophic levels suggest the possibility of multiple ingestion pathways. These include exposure from polluted seawater and sediments and/or additional trophic transfer from contaminated prey/forage items. We assess the likelihood that microplastic ingestion presents a significant conservation problem at current levels compared to other anthropogenic threats.

Genome-wide association study of primary open-angle glaucoma in continental and admixed African populations - Pieter W. M. Bonnemaijer; Adriana I. Iglesias; Girish N. Nadkarni; Anna J. Sanyiwa; Hassan G. Hassan; Colin Cook; Mark Simcoe; Kent D. Taylor; Claudia Schurmann; Gillian M. Belbin; Eimear E. Kenny; Erwin P. Bottinger; et al. (Human Genetics, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Correction to: Contrasting perspectives on the Lava Creek Tuff eruption, Yellowstone, from new U–Pb and 40Ar/39Ar age determinations - Colin J. N. Wilson; Mark E. Stelten; Jacob B. Lowenstern (Bulletin of Volcanology, 2018)

Contrasting perspectives on the Lava Creek Tuff eruption, Yellowstone, from new U–Pb and 40Ar/39Ar age determinations - Colin J. N. Wilson; Mark E. Stelten; Jacob B. Lowenstern (Bulletin of Volcanology, 2018)

Multifactorial roles of interannual variability, season, and sex for foraging patterns in a sexually size monomorphic seabird, the Australasian gannet (Morus serrator) - Diana Besel; Mark E. Hauber; Colin Hunter; Tamsin Ward-Smith; David Raubenheimer; Craig D. Millar; Stefanie M. H. Ismar (Marine Biology, 2018)

Barriers and Solutions to Conducting Large International, Interdisciplinary Research Projects - Erin C. Pischke; Jessie L. Knowlton; Colin C. Phifer; Jose Gutierrez Lopez; Tamara S. Propato; Amarella Eastmond; Tatiana Martins de Souza; Mark Kuhlberg; Valentin Picasso Risso; Santiago R. Veron; Carlos Garcia; Marta Chiappe; et al. (Environmental Management, 2017)

The biogeographical history of the interaction between mycoheterotrophic Thismia (Thismiaceae) plants and mycorrhizal Rhizophagus (Glomeraceae) fungi - Vincent S. F. T. Merckx; Sofia I. F. Gomes; Mark Wapstra; Colin Hunt; Greg Steenbeeke; Constantijn B. Mennes; Neville Walsh; Rob Smissen; Tsung‐Hsin Hsieh; Erik F. Smets; Martin I. Bidartondo (Journal of Biogeography, 2017)
Aim Achlorophyllous mycoheterotrophic plants and mycorrhizal fungi often have highly specific interactions that potentially limit the plants’ distribution and diversification potential. However, specificity in biotic interactions may differ considerably over a species’ distribution range and therefore interactions need to be studied over their entire range to assess their evolution in space and time. The present study investigates the biogeographical history of the interaction between five closely related mycoheterotrophic Thismia species and arbuscular mycorrhizal fungi over the distribution range of the plant species. Location Temperate south‐east Australia and New Zealand. Methods Phylogenetic relationships of Thismia (nr ITS and mt cob ) and their arbuscular mycorrhizal fungi (partial nr SSU ) were reconstructed based on data from 65 plant specimens. The diversification times in Thismia were estimated with a Bayesian relaxed clock approach using a Dioscoreales framework (nr SSU , mt atp1 , mt matR , mt nad1 b‐c ). Ancestral geographical ranges were reconstructed using a maximum likelihood approach. The same approach was used to reconstruct ancestral mycorrhizal associations. Results Our analysis shows that Thismia plants have highly specific, phylogenetically conserved and evolutionarily persistent interactions with Rhizophagus fungi. Nevertheless, Thismia was able to diversify and radiate recently due to the wide geographical distribution of the host fungi. In addition, we find that although the mycorrhizal interactions of this clade of mycoheterotrophs are strictly bound to a fungal lineage, host switches remain possible. Main conclusions In this clade of closely related mycoheterotrophs, dependency on highly specific fungal interactions is the result of phylogenetic niche conservatism, acting over at least 12 million years. Nevertheless, plants that are dependent on highly specific fungal interactions have ample opportunities to disperse and radiate over the geographical range of their hosts. Our study highlights the need to link the ecology and evolution of species interactions over broad geographical and evolutionary scales for understanding mycorrhizal interactions.

Project Recover: Extending the Applications of Unmanned Platforms and Autonomy to Support Underwater MIA Searches - Eric Terrill; Mark Moline; Patrick Scannon; Eric Gallimore; Travis Shramek; Andy Nager; Robert Hess; Megan Cimino; Patrick Colin; Andrew Pietruszka; Mark Anderson (Oceanography, 2017)

Morphological assessment of the Octopus vulgaris species complex evaluated in light of molecular‐based phylogenetic inferences - Michael D. Amor; Mark D. Norman; Alvaro Roura; Tatiana S. Leite; Ian G. Gleadall; Amanda Reid; Catalina Perales‐Raya; Chung‐Cheng Lu; Colin J. Silvey; Erica A. G. Vidal; Frederick G. Hochberg; Xiaodong Zheng; et al. (Zoologica Scripta, 2017)
Cryptic species are common in the ocean, particularly among marine invertebrates such as octopuses. Delineating cryptic species is particularly problematic in octopus taxonomy where the plasticity recorded among taxonomic characters often results in low resolution at the species level. This study investigated the morphological relationships among seven phylogenetic clades (identified using cytochrome c oxidase subunit I) of the broadly distributed Octopus vulgaris species complex and close relatives. Morphological analyses in this study were successful in delimiting O. sinensis , Brazilian O . vulgaris and O. vulgaris sensu stricto , which was congruent with the molecular findings of this study. Analyses based on male morphology were successful in distinguishing 14 of 15 total pairwise comparisons and proved to be a more reliable indicator of species‐level relationships in comparison with female morphology. The majority of characters with the greatest discriminatory power were male sexual traits. Significant morphological differences were also recorded among sampling localities of conspecifics, with phenotype showing correlation with local environmental data. The findings of this study support the hypothesis that multiple O. vulgaris ‐like species are currently being incorrectly treated under a single species name, O. vulgaris . Octopuses being exported globally under the name O. vulgaris are of extremely high fisheries market value and profile. Our findings have potentially significant implications for the naming and conservation of commercially harvested members of this species complex throughout their ranges.

Marine Microalgae: Climate, Energy, and Food Security from the Sea - Charles Greene; Mark Huntley; Ian Archibald; Léda Gerber; Deborah Sills; Joe Granados; Jefferson Tester; Colin Beal; Michael Walsh; Robert Bidigare; Susan Brown; William Cochlan; et al. (Oceanography, 2016)

Using mass-emergence devices to introduce an insect biocontrol agent to a new region and assist its dispersal - Scott Hardwick; Colin M. Ferguson; Mark R. McNeill; Craig B. Phillips (Journal of Pest Science, 2016)

The piggybacking stingray - Mark G. Meekan; Luke Trevitt; Colin A. Simpfendorfer; William White (Coral Reefs, 2016)

Genetic mapping of SrCad and SNP marker development for marker-assisted selection of Ug99 stem rust resistance in wheat - Mulualem T. Kassa; Frank M. You; Tom G. Fetch; Pierre Fobert; Andrew Sharpe; Curtis J. Pozniak; James G. Menzies; Mark C. Jordan; Gavin Humphreys; Tingting Zhu; Ming-Cheng Luo; Curt A. McCartney; et al. (Theoretical and Applied Genetics, 2016)

A Digital Repository and Execution Platform for Interactive Scholarly Publications in Neuroscience - Victoria Hodge; Mark Jessop; Martyn Fletcher; Michael Weeks; Aaron Turner; Tom Jackson; Colin Ingram; Leslie Smith; Jim Austin (Neuroinformatics, 2016)

Sea turtles return home after intentional displacement from coastal foraging areas - Takahiro Shimada; Colin Limpus; Rhondda Jones; Julia Hazel; Rachel Groom; Mark Hamann (Marine Biology, 2016)

Tsunami forcing by a low Froude number landslide - Colin Whittaker; Roger Nokes; Mark Davidson (Environmental Fluid Mechanics, 2015)

Publishing and sharing multi-dimensional image data with OMERO - Jean-Marie Burel; Sébastien Besson; Colin Blackburn; Mark Carroll; Richard K. Ferguson; Helen Flynn; Kenneth Gillen; Roger Leigh; Simon Li; Dominik Lindner; Melissa Linkert; William J. Moore; et al. (Mammalian Genome, 2015)

Fine mapping and identification of a candidate gene for the barley Un8 true loose smut resistance gene - Wen Zang; Peter E. Eckstein; Mark Colin; Doug Voth; Axel Himmelbach; Sebastian Beier; Nils Stein; Graham J. Scoles; Aaron D. Beattie (Theoretical and Applied Genetics, 2015)

Proceedings of the second international molecular pathological epidemiology (MPE) meeting - Shuji Ogino; Peter T. Campbell; Reiko Nishihara; Amanda I. Phipps; Andrew H. Beck; Mark E. Sherman; Andrew T. Chan; Melissa A. Troester; Adam J. Bass; Kathryn C. Fitzgerald; Rafael A. Irizarry; Karl T. Kelsey; et al. (Cancer Causes & Control, 2015)

Climate change implications in the northern coastal temperate rainforest of North America - Colin S. Shanley; Sanjay Pyare; Michael I. Goldstein; Paul B. Alaback; David M. Albert; Colin M. Beier; Todd J. Brinkman; Rick T. Edwards; Eran Hood; Andy MacKinnon; Megan V. McPhee; Trista M. Patterson; et al. (Climatic Change, 2015)

A new method to generate a high-resolution global distribution map of lake chlorophyll - Michael J. Sayers; Amanda G. Grimm; Robert A. Shuchman; Andrew M. Deines; David B. Bunnell; Zachary B. Raymer; Mark W. Rogers; Whitney Woelmer; David H. Bennion; Colin N. Brooks; Matthew A. Whitley; David M. Warner; et al. (International Journal of Remote Sensing, 2015)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Erratum to: EURO-CORDEX: new high-resolution climate change projections for European impact research - Daniela Jacob; Juliane Petersen; Bastian Eggert; Antoinette Alias; Ole Bøssing Christensen; Laurens M. Bouwer; Alain Braun; Augustin Colette; Michel Déqué; Goran Georgievski; Elena Georgopoulou; Andreas Gobiet; et al. (Regional Environmental Change, 2014)

EURO-CORDEX: new high-resolution climate change projections for European impact research - Daniela Jacob; Juliane Petersen; Bastian Eggert; Antoinette Alias; Ole Bøssing Christensen; Laurens M. Bouwer; Alain Braun; Augustin Colette; Michel Déqué; Goran Georgievski; Elena Georgopoulou; Andreas Gobiet; et al. (Regional Environmental Change, 2014)

The effects of aerobic exercise training at two different intensities in obesity and type 2 diabetes: implications for oxidative stress, low-grade inflammation and nitric oxide production - Mauricio Krause; Josianne Rodrigues-Krause; Ciara O’Hagan; Paul Medlow; Gareth Davison; Davide Susta; Colin Boreham; Philip Newsholme; Mark O’Donnell; Colin Murphy; Giuseppe De Vito (European Journal of Applied Physiology, 2014)

3D representation of geochemical data, the corresponding alteration and associated REE mobility at the Ranger uranium deposit, Northern Territory, Australia - Louise A. Fisher; James S. Cleverley; Mark Pownceby; Colin MacRae (Mineralium Deposita, 2013)

Protected area networks and savannah bird biodiversity in the face of climate change and land degradation - Colin M. Beale; Neil E. Baker; Mark J. Brewer; Jack J. Lennon (Ecology Letters, 2013)
The extent to which climate change might diminish the efficacy of protected areas is one of the most pressing conservation questions. Many projections suggest that climate‐driven species distribution shifts will leave protected areas impoverished and species inadequately protected while other evidence suggests that intact ecosystems within protected areas will be resilient to change. Here, we tackle this problem empirically. We show how recent changes in distribution of 139 Tanzanian savannah bird species are linked to climate change, protected area status and land degradation. We provide the first evidence of climate‐driven range shifts for an African bird community. Our results suggest that the continued maintenance of existing protected areas is an appropriate conservation response to the challenge of climate and environmental change.

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Plant growth rates and seed size: a re‐evaluation - Lindsay A. Turnbull; Christopher D. Philipson; Drew W. Purves; Rebecca L. Atkinson; Jennifer Cunniff; Anne Goodenough; Yann Hautier; Jennie Houghton; Toby R. Marthews; Colin P. Osborne; Cloé Paul-Victor; Karen E. Rose; et al. (Ecology, 2012)
Small‐seeded plant species are often reported to have high relative growth rate or RGR. However, because RGR declines as plants grow larger, small‐seeded species could achieve higher RGR simply by virtue of their small size. In contrast, size‐standardized growth rate or SGR factors out these size effects. Differences in SGR can thus only be due to differences in morphology, allocation, or physiology. We used nonlinear regression to calculate SGR for comparison with RGR for 10 groups of species spanning a wide range of life forms. We found that RGR was negatively correlated with seed mass in nearly all groups, but the relationship between SGR and seed mass was highly variable. We conclude that small‐seeded species only sometimes possess additional adaptations for rapid growth over and above their general size advantage.

Light detection and ranging (LiDAR) and multispectral studies of disturbed Lake Superior coastal environments - W. Charles Kerfoot; Foad Yousef; Sarah A. Green; Robert Regis; Robert Shuchman; Colin N. Brooks; Mike Sayers; Bruce Sabol; Mark Graves (Limnology and Oceanography, 2012)
Due to its high spatial resolution and excellent water penetration, coastal light detection and ranging (LiDAR) coupled with multispectral imaging (MSS) has great promise for resolving shoreline features in the Great Lakes. Previous investigations in Lake Superior documented a metal‐rich “halo” around the Keweenaw Peninsula, related to past copper mining practices. Grand Traverse Bay on the Keweenaw Peninsula provides an excellent Great Lakes example of global mine discharges into coastal environments. For more than a century, waste rock migrating from shoreline tailings piles has moved along extensive stretches of coast, damming stream outlets, intercepting wetlands and recreational beaches, suppressing benthic invertebrate communities, and threatening critical fish breeding grounds. In the bay, the magnitude of the discarded wastes literally “reset the shoreline” and provided an intriguing field experiment in coastal erosion and spreading environmental effects. Employing a combination of historic aerial photography and LiDAR, we estimate the time course and mass of tailings eroded into the bay and the amount of copper that contributed to the metal‐rich halo. We also quantify underwater tailings spread across benthic substrates by using MSS imagery on spectral reflectance differences between tailings and natural sediment types, plus a depth‐correction algorithm (Lyzenga Method). We show that the coastal detail from LiDAR and MSS opens up numerous applications for ecological, ecosystem, and geological investigations.

Quantifying the effect of soil compaction on three varieties of wheat (Triticum aestivum L.) using X-ray Micro Computed Tomography (CT) - Saoirse R. Tracy; Colin R. Black; Jeremy A. Roberts; Ann McNeill; Rob Davidson; Mark Tester; Marko Samec; Dean Korošak; Craig Sturrock; Sacha J. Mooney (Plant and Soil, 2012)

Plant extinction risk under climate change: are forecast range shifts alone a good indicator of species vulnerability to global warming? - Damien A. Fordham; H. Resit Akçakaya; Miguel B. Araújo; Jane Elith; David A. Keith; Richard Pearson; Tony D. Auld; Camille Mellin; John W. Morgan; Tracey J. Regan; Mark Tozer; Michael J. Watts; et al. (Global Change Biology, 2012)
Models that couple habitat suitability with demographic processes offer a potentially improved approach for estimating spatial distributional shifts and extinction risk under climate change. Applying such an approach to five species of Australian plants with contrasting demographic traits, we show that: (i) predicted climate‐driven changes in range area are sensitive to the underlying habitat model, regardless of whether demographic traits and their interaction with habitat patch configuration are modeled explicitly; and (ii) caution should be exercised when using predicted changes in total habitat suitability or geographic extent to infer extinction risk, because the relationship between these metrics is often weak. Measures of extinction risk, which quantify threats to population persistence, are particularly sensitive to life‐history traits, such as recruitment response to fire, which explained approximately 60% of the deviance in expected minimum abundance. Dispersal dynamics and habitat patch structure have the strongest influence on the amount of movement of the trailing and leading edge of the range margin, explaining roughly 40% of modeled structural deviance. These results underscore the need to consider direct measures of extinction risk (population declines and other measures of stochastic viability), as well as measures of change in habitat area, when assessing climate change impacts on biodiversity. Furthermore, direct estimation of extinction risk incorporates important demographic and ecosystem processes, which potentially influence species’ vulnerability to extinction due to climate change.

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

The efficacy of detecting variants with small effects on the Affymetrix 6.0 platform using pooled DNA - Charleston W. K. Chiang; Zofia K. Z. Gajdos; Joshua M. Korn; Johannah L. Butler; Rachel Hackett; Candace Guiducci; Thutrang T. Nguyen; Rainford Wilks; Terrence Forrester; Katherine D. Henderson; Loic Le Marchand; Brian E. Henderson; et al. (Human Genetics, 2011)

Expansion of human mesenchymal stem cells on microcarriers - Christopher J. Hewitt; Ken Lee; Alvin W. Nienow; Robert J. Thomas; Mark Smith; Colin R. Thomas (Biotechnology Letters, 2011)

Enhanced decomposition of selenium hyperaccumulator litter in a seleniferous habitat—evidence for specialist decomposers? - Colin F. Quinn; Karl A. Wyant; Ami L. Wangeline; Jeremy Shulman; Miriam L. Galeas; Jose Rodolfo Valdez; James R. Self; Mark W. Paschke; Elizabeth A. H. Pilon-Smits (Plant and Soil, 2011)

Pre-Colombian Mercury Pollution Associated with the Smelting of Argentiferous Ores in the Bolivian Andes - Colin A. Cooke; Prentiss H. Balcom; Charles Kerfoot; Mark B. Abbott; Alexander P. Wolfe (Ambio, 2011)

Resource allocation for efficient environmental management - Michael A. McCarthy; Colin J. Thompson; Cindy Hauser; Mark A. Burgman; Hugh P. Possingham; Melinda L. Moir; Thanawat Tiensin; Marius Gilbert (Ecology Letters, 2010)
Ecology Letters (2010) Abstract Environmental managers must decide how to invest available resources. Researchers have previously determined how to allocate conservation resources among regions, design nature reserves, allocate funding to species conservation programs, design biodiversity surveys and monitoring programs, manage species and invest in greenhouse gas mitigation schemes. However, these issues have not been addressed with a unified theory. Furthermore, uncertainty is prevalent in environmental management, and needs to be considered to manage risks. We present a theory for optimal environmental management, synthesizing previous approaches to the topic and incorporating uncertainty. We show that the theory solves a diverse range of important problems of resource allocation, including distributing conservation resources among the world’s biodiversity hotspots; surveillance to detect the highly pathogenic avian influenza H5N1 virus in Thailand; and choosing survey methods for the insect order Hemiptera. Environmental management decisions are similar to decisions about financial investments, with trade‐offs between risk and reward.

Changes in the distribution of native fishes in response to introduced species and other anthropogenic effects - Evelyn Habit; Priscila Piedra; Daniel E. Ruzzante; Sandra J. Walde; Mark C. Belk; Víctor E. Cussac; Jorge Gonzalez; Nicole Colin (Global Ecology and Biogeography, 2010)
Aim Globally, one of the major threats to the integrity of native faunas is the loss of biodiversity that can result from the introduction of exotics. Here we document recent changes in the distribution of five common fish species that are linked to introductions in Chile. Location Chile from 28° S to 54° S. Methods We assess the extent of changes in distribution of galaxiid species by comparing their historical and current distributions based on the results of the most extensive survey of freshwater fishes in Chile to date, a range that encompasses the full latitudinal and elevational range of the Galaxiidae in Chile. We test for relationships of the distributions and abundances of native fishes with the incidence of introduced species. Results The latitudinal range of Galaxias maculatus has declined by 26%, and most of this reduction has occurred in the northern part of its range. Aplochiton taeniatus and Brachygalaxias bullocki have experienced reductions (8–17% loss) in total drainage area occupied, and they have disappeared from, or are now extremely difficult to find, in latitudes 36° to 41° S, coincidently with areas of urban growth and intense economic activities. The distribution of Galaxias platei has, instead, increased considerably. In northern basins, G. maculatus has apparently been replaced by an introduced poeciliid Gambusia sp. High‐elevation systems remain dominated by native Galaxias platei , whereas systems at intermediate elevations, especially rivers, are now dominated by introduced salmonids. Within drainages, native galaxiids remain abundant where exotic salmonid abundance is low. Main conclusions We suggest that negative interactions between introduced and native fish are responsible for some of the range reductions among Galaxiidae in Chile. The severity of the impacts varies with latitude and altitude and is probably related to temperature. The effects of Gambusia are restricted to warmer systems. Native fish also appear to have found temperature refugia from salmonids; impacts are low in the warmer northern and coastal systems, as well as in high‐altitude relatively cold systems. Native fish also appear less vulnerable to salmonids in lakes than in rivers. This study identifies watersheds critical for the conservation of biodiversity within the Galaxiidae.

A virgin flight across the Tasman Sea? Satellite tracking of post-fledging movement in the Australasian Gannet Morus serrator - Stefanie M. H. Ismar; Colin Hunter; Kevin Lay; Tamsin Ward-Smith; Peter R. Wilson; Mark E. Hauber (Journal of Ornithology, 2010)

Growth and chemical defense in willow seedlings: trade-offs are transient - Colin Mark Orians; Cris G. Hochwender; Robert S. Fritz; Tord Snäll (Oecologia, 2010)

Climate change and long‐term data are the hot topics at Auckland conference on ‘Climate and Oceans’ - Mark J Costello; Mary Livingston; Colin McLay; Ann McCrone; Carolyn Lundquist (New Zealand Journal of Marine and Freshwater Research, 2010)

Regression analysis of spatial data - Colin M. Beale; Jack J. Lennon; Jon M. Yearsley; Mark J. Brewer; David A. Elston (Ecology Letters, 2010)
Ecology Letters (2010) 13: 246–264 Abstract Many of the most interesting questions ecologists ask lead to analyses of spatial data. Yet, perhaps confused by the large number of statistical models and fitting methods available, many ecologists seem to believe this is best left to specialists. Here, we describe the issues that need consideration when analysing spatial data and illustrate these using simulation studies. Our comparative analysis involves using methods including generalized least squares, spatial filters, wavelet revised models, conditional autoregressive models and generalized additive mixed models to estimate regression coefficients from synthetic but realistic data sets, including some which violate standard regression assumptions. We assess the performance of each method using two measures and using statistical error rates for model selection. Methods that performed well included generalized least squares family of models and a Bayesian implementation of the conditional auto‐regressive model. Ordinary least squares also performed adequately in the absence of model selection, but had poorly controlled Type I error rates and so did not show the improvements in performance under model selection when using the above methods. Removing large‐scale spatial trends in the response led to poor performance. These are empirical results; hence extrapolation of these findings to other situations should be performed cautiously. Nevertheless, our simulation‐based approach provides much stronger evidence for comparative analysis than assessments based on single or small numbers of data sets, and should be considered a necessary foundation for statements of this type in future.

Secondary woody vegetation patterns in New Zealand's South Island dryland zone - Susan Walker; Nigel King; Adrian Monks; Sophie Williams; Larry Burrows; Ellen Cieraad; Colin Meurk; Jacob McC Overton; Robbie Price; Mark Smale (New Zealand Journal of Botany, 2009)
Can New Zealand's indigenous dryland ecosystems be rehabilitated by facilitating inherent successional tendencies to enhance development of indigenous‐dominated and often woody communities in the long term? Here, we describe the geographic distribution of woody communities of New Zealand's South Island drylands to generate hypotheses about successional trajectories to future vegetation states. Presences and absences of woody species in 3880 vegetation plots collated from past surveys were used to predict species potential distributions across drylands. Separate models and spatial predictions were built for each of four classes of woody richness, which were used as surrogates for successional stages. Woody species richness increased significantly from grassland to shrubland and from shrubland to forest cover, and trends in species traits also suggest richness class was related with successional stage. Indigenous woody species outnumbered exotic species in all richness classes. Assuming richness classes represent temporal progressions, our results suggest relatively homogeneous early‐successional woody associations succeed to a divergent array of woody associations in different environments. Growth forms of species in our predicted associations suggest transitions from grassland to tall, tree‐rich forests in northern and coastal drylands, and to liane‐rich open or lightcanopied shrubland, woodland, or low forest in more severe inland environments. These putative communities are novel in species composition but physiognomically broadly similar to pre‐settlement analogues. Especially in severe inland environments, unassisted transitions from grassland to indigenousdominated late‐successional woody communities may depend on the exclusion of tall exotic trees, Scotch broom, and gorse in early succession.

An inter-laboratory comparison of multi-enzyme and multiple substrate-induced respiration assays to assess method consistency in soil monitoring - Rachel E. Creamer; Pat Bellamy; Helaina I. J. Black; Clare M. Cameron; Colin D. Campbell; Paul Chamberlain; Jim Harris; Nisha Parekh; Mark Pawlett; Jan Poskitt; Dote Stone; Karl Ritz (Biology and Fertility of Soils, 2009)

The enzymatic basis for pesticide bioremediation - Colin Scott; Gunjan Pandey; Carol J. Hartley; Colin J. Jackson; Matthew J. Cheesman; Matthew C. Taylor; Rinku Pandey; Jeevan L. Khurana; Mark Teese; Chris W. Coppin; Kahli M. Weir; Rakesh K. Jain; et al. (Indian Journal of Microbiology, 2008)

In search of a functional flora—towards a greater integration of ecology and taxonomy - Colin A. Pendry; Jan Dick; Martin R. Pullan; Sabina G. Knees; Anthony G. Miller; Sophie Neale; Mark F. Watson (Plant Ecology, 2007)

Projected Changes in Terrestrial Carbon Storage in Europe under Climate and Land-use Change, 1990–2100 - Sönke Zaehle; Alberte Bondeau; Timothy R. Carter; Wolfgang Cramer; Markus Erhard; I. Colin Prentice; I. Reginster; Mark D. A. Rounsevell; Stephen Sitch; Benjamin Smith; Pascalle C. Smith; Martin Sykes (Ecosystems, 2007)

Environmental change and the phenology of European aphids - RICHARD HARRINGTON; SUZANNE J. CLARK; SUE J. WELHAM; PAUL J. VERRIER; COLIN H. DENHOLM; MAURICE HULLÉ; DAMIEN MAURICE; MARK D. ROUNSEVELL; NADÈGE COCU (Global Change Biology, 2007)
Aphids, because of their short generation time and low developmental threshold temperatures, are an insect group expected to respond particularly strongly to environmental changes. Forty years of standardized, daily data on the abundance of flying aphids have been brought together from countries throughout Europe, through the EU Thematic Network ‘EXAMINE’. Relationships between phenology, represented by date of first appearance in a year in a suction trap, of 29 aphid species and environmental data have been quantified using the residual maximum likelihood (REML) methodology. These relationships have been used with climate change scenario data to suggest plausible changes in aphid phenology. In general, the date of first record of aphid species in suction traps is expected to advance, the rate of advance varying with location and species, but averaging 8 days over the next 50 years. Strong relationships between aphid phenology and environmental variables have been found for many species, but they are notably weaker in species living all year on trees. Canonical variate analysis and principal coordinate analysis were used to determine ordinations of the 29 species on the basis of the presence/absence of explanatory variables in the REML models. There was strong discrimination between species with different life cycle strategies and between species feeding on herbs and trees, suggesting the possible value of trait‐based groupings in predicting responses to environmental changes.

Longitudinal changes in biota along four New Zealand streams: Declines and improvements in stream health related to land use - Dev K. Niyogi; Mark Koren; Chris J. Arbuckle; Colin R. Townsend (New Zealand Journal of Marine and Freshwater Research, 2007)
We studied four streams in southern New Zealand in 2002 to document downstream changes in water quality, habitat, and stream biota in relation to land use. Two streams were in catchments that had increasing intensity of agricultural development downstream from relatively pristine headwaters. A third stream had the most intense land use in the headwaters and a riparian corridor of regenerating native forest along its middle reaches. A fourth stream had low intensity pasturing in its lower reaches, but also downstream increases in sedimentation from natural and historic mining sources. Four to six sites were sampled along each stream. Pastoral land cover in catchments was positively related to nutrient concentrations and fine sediment cover in the streams. At the most agricultural sites, dissolved inorganic nitrogen reached concentrations of 2 mg/litre, and fine sediment covered 33% of the stream bottom. Several biotic indices for invertebrates, including the Macroinvertebrate Community Index (MCI), were lower at the agricultural sites, which had MCI scores around 100. The indices were negatively related to fine sediment cover. The site with the intact riparian zone had declines in sedimentation downstream, which were paralleled by increases in invertebrate richness and biotic indices. Our findings support the notion that the restoration of riparian zones can improve stream habitat and invertebrate health.

Stream Communities Along a Catchment Land-Use Gradient: Subsidy-Stress Responses to Pastoral Development - Dev K. Niyogi; Mark Koren; Chris J. Arbuckle; Colin R. Townsend (Environmental Management, 2007)

Domestication potential and marketing of Canarium indicum nuts in the Pacific: 1. A literature review - Tio Nevenimo; John Moxon; John Wemin; Mark Johnston; Colin Bunt; R. R. B. Leakey (Agroforestry Systems, 2007)

Rational Design of a Dual-Mode Optical and Chemical Prodrug - Colin P. McCoy; Clare Rooney; David S. Jones; Sean P. Gorman; Mark Nieuwenhuyzen (Pharmaceutical Research, 2006)

Specificity of Phenolic Glycoside Induction in Willow Seedlings (Salix sericea) in Response to Herbivory - Mark J. Fields; Colin M. Orians (Journal of Chemical Ecology, 2006)

A genetic test for recruitment enhancement in Chesapeake Bay oysters, Crassostrea virginica, after population supplementation with a disease tolerant strain - Matthew P. Hare; Standish K. Allen; Paulette Bloomer; Mark D. Camara; Ryan B. Carnegie; Jenna Murfree; Mark Luckenbach; Donald Meritt; Cheryl Morrison; Kennedy Paynter; Kimberly S. Reece; Colin G. Rose (Conservation Genetics, 2006)

Regional and annual variation in plasma steroids and metabolic indicators in female green turtles, Chelonia mydas - Mark Hamann; Tim S. Jessop; Colin J. Limpus; Joan M. Whittier (Marine Biology, 2005)

‘Modelling the Arctic Boundary Layer: An Evaluation of Six Arcmip Regional-Scale Models using Data from the Sheba Project’ - Michael Tjernström; Mark Žagar; Gunilla Svensson; John J. Cassano; Susanne Pfeifer; Annette Rinke; Klaus Wyser; Klaus Dethloff; Colin Jones; Tido Semmler; Michael Shaw (Boundary-Layer Meteorology, 2005)

Bacterial diversity in the bacterioneuston (sea surface microlayer): the bacterioneuston through the looking glass - Mark P. Franklin; Ian R. McDonald; David G. Bourne; Nicholas J. P. Owens; Robert C. Upstill‐Goddard; J. Colin Murrell (Environmental Microbiology, 2005)
Summary The bacterioneuston is defined as the community of bacteria present within the neuston or sea surface microlayer. Bacteria within this layer were sampled using a membrane filter technique and bacterial diversity was compared with that in the underlying pelagic coastal seawater using molecular ecological techniques. 16S rRNA gene libraries of ≈ 500 clones were constructed from both bacterioneuston and the pelagic water samples and representative clones from each library were sequenced for comparison of bacterial diversity. The bacterioneuston was found to have a significantly lower bacterial diversity than the pelagic seawater, with only nine clone types (ecotaxa) as opposed to 46 ecotaxa in the pelagic seawater library. Surprisingly, the bacterioneuston clone library was dominated by 16S rRNA gene sequences affiliated to two groups of organisms, Vibrio spp. which accounted for over 68% of clones and Pseudoalteromonas spp. accounting for 21% of the library. The dominance of these two 16S rRNA gene sequence types within the bacterioneuston clone library was confirmed in a subsequent gene probing experiment. 16S rRNA gene probes specific for these groups of bacteria were designed and used to probe new libraries of 1000 clones from both the bacterioneuston and pelagic seawater DNA samples. This revealed that 57% of clones from the bacterioneuston library hybridized to a Vibrio sp.‐specific 16S rRNA gene probe and 32% hybridized to a Pseudoalteromonas sp.‐specific 16S rRNA gene probe. In contrast, the pelagic seawater library resulted in only 13% and 8% of 16S rRNA gene clones hybridizing to the Vibrio sp. and Pseudoalteromonas sp. probes respectively. Results from this study suggest that the bacterioneuston contains a distinct population of bacteria and warrants further detailed study at the molecular level.

Y chromosome haplogroups of elite Ethiopian endurance runners - Colin N. Moran; Robert A. Scott; Susan M. Adams; Samantha J. Warrington; Mark A. Jobling; Richard H. Wilson; William H. Goodwin; Evelina Georgiades; Bezabhe Wolde; Yannis P. Pitsiladis (Human Genetics, 2004)

USE OF A PETHIDINE AND MIDAZOLAM COMBINATION FOR THE REVERSIBLE SEDATION OF CRABEATER SEALS (LOBODON CARCINOPHAGUS) - Mark A. Tahmindjis; Damien P. Higgins; Michael J. Lynch; Julie A. Barnes; Colin J. Southwell (Marine Mammal Science, 2003)
A bstract Between October and December of 1996–1999, off eastern Antarctica (60°‐150°E), we darted 31 crabeater seals with midazolam and pethidine at estimated dose rates of 0.15–0.4 mg/kg and 1–3 mg/kg, respectively. Maximum sedation was reached at 23 ± 9 min (n = 18) and first signs of recovery were noted at 54 ± 24 min (n = 4). Seals greater than 250 kg body‐mass were sedated by administration of approximately 90–100 mg midazolam and 600 mg pethidine, but the degree of sedation was unpredictable and did not permit invasive procedures in some cases. Behavior of the seal and adjacent conspecifics affected the success of procedures and our ability to monitor vital signs. Naloxone and flumazenil reversed sedation, making this combination attractive for use in animals adjacent to water. Additional ketamine was administered to two seals, resulting in improved restraint.

Risks from Competitively Inferior Immigrant Populations: Implications of Mass Effects for Species Conservation - Colin J. Thompson; Ben J. P. Thompson; Mark A. Burgman (Conservation Biology, 2003)
Many species are maintained by a rain of propagules from a source population and thereby persist in a location from which they would ordinarily be excluded by competition. This is one explanation for the persistence of competitively inferior domestic species in natural environments. The purpose of our study was to estimate the effect of immigrant populations on competitively superior wild species in terms of the risks of decline—the quasiextinction risk—of the wild population and the quasiexplosion risk of the immigrant population. A simple mathematical model of escape and competition demonstrates that the risks to a wild population may be appreciable. We found that even when the species maintained by mass effects is not viable in the absence of competition and immigration, low escape rates ( e.g., enough to give the invasive population a net positive growth rate ) can make a wild‐competing species vulnerable within 10 years. The probability that the immigrant population will exceed lower bounds increases rapidly with rates of escape and growth.

Genetic, physical, and phenotypic characterization of the Del(13)Svea36H mouse - Ruth M. Arkell; Matthew Cadman; Tracy Marsland; Anne Southwell; Caroline Thaung; Jennifer R. Davies; Toni Clay; Colin V. Beechey; Edward P. Evans; Mark A. Strivens; Steve D.M. Brown; Paul Denny (Mammalian Genome, 2001)

Compound heterozygosity and nonsense mutations in the α1-subunit of the inhibitory glycine receptor in hyperekplexia - Mark I. Rees; Trevor M. Lewis; Behnaz Vafa; Colin Ferrie; Peter Corry; Fransesco Muntoni; Heinz Jungbluth; John B. Stephenson; Mike Kerr; Russell G. Snell; Peter R. Schofield; Michael J. Owen (Human Genetics, 2001)

Global response of terrestrial ecosystem structure and function to CO 2 and climate change: results from six dynamic global vegetation models - Wolfgang Cramer; Alberte Bondeau; F. Ian Woodward; I. Colin Prentice; Richard A. Betts; Victor Brovkin; Peter M. Cox; Veronica Fisher; Jonathan A. Foley; Andrew D. Friend; Chris Kucharik; Mark R. Lomas; et al. (Global Change Biology, 2001)
Summary The possible responses of ecosystem processes to rising atmospheric CO 2 concentration and climate change are illustrated using six dynamic global vegetation models that explicitly represent the interactions of ecosystem carbon and water exchanges with vegetation dynamics. The models are driven by the IPCC IS92a scenario of rising CO 2 ( Wigley et al . 1991 ), and by climate changes resulting from effective CO 2 concentrations corresponding to IS92a, simulated by the coupled ocean atmosphere model HadCM2‐SUL. Simulations with changing CO 2 alone show a widely distributed terrestrial carbon sink of 1.4–3.8 Pg C y −1 during the 1990s, rising to 3.7–8.6 Pg C y −1 a century later. Simulations including climate change show a reduced sink both today (0.6–3.0 Pg C y −1 ) and a century later (0.3–6.6 Pg C y −1 ) as a result of the impacts of climate change on NEP of tropical and southern hemisphere ecosystems. In all models, the rate of increase of NEP begins to level off around 2030 as a consequence of the ‘diminishing return’ of physiological CO 2 effects at high CO 2 concentrations. Four out of the six models show a further, climate‐induced decline in NEP resulting from increased heterotrophic respiration and declining tropical NPP after 2050. Changes in vegetation structure influence the magnitude and spatial pattern of the carbon sink and, in combination with changing climate, also freshwater availability (runoff). It is shown that these changes, once set in motion, would continue to evolve for at least a century even if atmospheric CO 2 concentration and climate could be instantaneously stabilized. The results should be considered illustrative in the sense that the choice of CO 2 concentration scenario was arbitrary and only one climate model scenario was used. However, the results serve to indicate a range of possible biospheric responses to CO 2 and climate change. They reveal major uncertainties about the response of NEP to climate change resulting, primarily, from differences in the way that modelled global NPP responds to a changing climate. The simulations illustrate, however, that the magnitude of possible biospheric influences on the carbon balance requires that this factor is taken into account for future scenarios of atmospheric CO 2 and climate change.

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

The role ofc-type cytochromes in the terminal respiratory chain of the methylotrophic bacteriumMethylophilus methylotrophus - Mark A. Carver; Colin W. Jones (Archives of Microbiology, 1984)